Ventilation circuit for large and gassy longwall panels – an Australian perspective. (December 2013) - Halim, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The current trend in Australian longwall mines is to increase panel dimensions and production rate, and mining in gassy regions. However, this trend poses a challenge to provide adequate ventilation to manage gas emissions. While the traditional two heading gateroad bleederless U ventilation circuit, which is the most commonly used circuit in Australia, is no longer suitable due to its low volumetric capacity, a few mines manage to overcome this problem by employing a three heading gateroad ventilation circuit. However, this circuit requires significant additional development, which makes it not popular in Australian coal mines. The aim of this paper is to review the suitability of two heading and three heading gateroad traditional bleederless U ventilation circuits for a large longwall panel mining in gassy conditions. It was found that significant predrainage of the thickest roof seam is required in order to make the two heading gateroad circuit feasible in large and gassy longwall panels.